Assessment of physical activity level in diabetes mellitus patients: A cross-sectional study at the tertiary hospital - Giri, Rajendra Mani; Joshi, Mukesh; Jha, Rohit; Sah, Pappu Kumar; Gautam, Sanjeev; Joshi, Sanjeev; Rokaya, Manish; Sharma, Sandip Kumar; Panthi, Ram Chandra (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Diabetes mellitus is a major public health concern globally and in Nepal, with a rising burden in rural and underserved regions such as Karnali Province. Physical activity is a key component of diabetes management, yet data from rural Nepal are limited. This study assessed physical activity levels among patients with diabetes mellitus attending a tertiary center and examined their association with glycemic control indicators. Methods: This was a cross-sectional study conducted in a tertiary care center of Nepal, among patients aged ≥20 years with diagnosed diabetes mellitus who attended the hospital during the study period of April 2025 to October 2025. Physical activity was assessed using a structured questionnaire adapted from the International Physical Activity Questionnaire. Glycemic control indicators (HbA1c, fasting blood glucose, and 2-hour postprandial blood glucose) were obtained from laboratory records. Following data collection, statistical analysis was conducted using SPSS 22 software. Descriptive statistics and chisquare tests were applied. Results: Among all participants (N = 145), about two-thirds (66.21%) had poor glycemic control, i.e., HbA1c≥ 6.5%. Nearly 67% reported engaging in more than 600 MET-minutes per week of moderate physical activity, meeting the WHO-recommended levels. Higher physical activity was significantly associated with lower fasting plasma glucose and with lower postprandial blood glucose, although the latter association was not statistically significant. Conclusion: Inadequate glycemic control remained common among diabetes patients and correlated poorly with glycemic control. Integrating physical activity promotion with routine clinical care and public health interventions is essential.